Evaluation of frontline demonstrations on rapeseed (Brassica napus L.) in south western district of Punjab - Nirmaljit Singh Dhaliwal; Gurmail Singh Sandhu; Karamjit Sharma (Journal of Oilseed Brassica, 2026)
Rapeseed-mustard is an important crop of India but its productivity is low due to poor knowledge level of the farmersregarding improved technologies. Frontline demonstrations are important tool for technology transfer to the farmers andits imperative to demonstrate high yielding, nutritionally better varieties to improve productivity. KVK, Sri MuktsarSahib conducted frontline demonstrations on new canola variety during 2015-16 with the objective to endorse canola,assessment of its performance in the district and to collect farmer’s feedback information. The results obtained from thestudy revealed that average yield of canola under FLDs was 19.3 q/ha as compare to 15.5 q/ha recorded in farmer’spractice thereby giving average yield increase of 24.2 per cent. Additional investment of Rs 1246 ha-1 along with scientificmonitoring of demonstrations resulted in additional return of Rs 13784 ha-1 over farmers practice.